Peculiarities of criminal radicalism determination among prisoners sentenced to imprisonment - P. Yu. Danylchenko (Bulletin of Kharkiv National University of Internal Affairs)
The article is devoted to the study of the criminal radicalism determination among convicts. It has been established and substantiated that this criminal phenomenon is linked to groups of cultural, psychological, organizational and managerial factors. It has been described and explained the content and role of elements of criminal subculture in the reproduction of criminal radicalism among convicts. Attention has been focused on the imperative of a negative attitude towards voluntary cooperation with representatives of the administration of penal institutions. The corresponding communication ban is based on the attitude of opposition to the state in general and law enforcement agencies in particular, on the internal consolidation of the criminal environment and direct or indirect opposition and personal opposition to law enforcement practices, including resocialization in penitentiary institutions.